Effects of Violent Video/Computer Games (Global Journal of Human-Social Science, 2016)
The research topic for this paper presented hereby is on the topic titled 'The effects of violent video/ computer games. My research paper basically focuses on the effects of playing violent video or computer games. For my research I also gathered primary and secondary data which shows the positive and negative effects of playing violent computer games.
Keywords: primary and secondary data